DYNAMIC STUDY BEHAVIOR OF THE FLUIDIZED BINARY MIXTURE BED WITH BENTONITE PARTICLES - GABRIELA MUNTIANU; ILEANA-DENISA NISTOR; ANA-MARIA GEORGESCU; ANA-MARIA ROȘU; DIANA-CARMEN MIRILĂ; ALINA MONICA MAREȘ; COSMIN VALERIU JINESCU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This study presents experimental data on the behavior of gas-solid systems in classical fluidization of simple particles and binary mixtures. Sodium and calcium bentonite particles with different physical properties were used to determine dynamic parameters. The use of bentonite particles is often recommended because they are easy to manipulate and have high specific surface areas for gas-solid contact. The study examines the influence of average particle diameter ( ) and bed height (H0) on bed porosity (ε0), pressure drop (ΔP), and minimum fluidization velocity (Umf). Bentonite particles in a fluidized bed belong to Groups B and D according to Geldart's classification. The binary mixture particles have the same diameter but different densities and are pseudo-homogeneously mixed. The minimum fluidization velocity for well-mixed particles (Umf,mix) was determined for two mixtures with 0.57 mass fraction of sodium bentonite and bed ratios (H0/D) close to 2. Experimental values for minimum pressure drop (ΔPmin), minimum fluidization velocity (Umf), and minimum fluidization velocity for the mixture were compared with theoretical values using empirical equations. Regression analysis of all experimental data provided an empirical model for Umf and Umf,mix. The study aims to achieve better dynamic conditions for efficient and effective use of binary mixtures in future adsorption processes.